EARLY DETECTION OF INCIDENT USING VEHICULAR AD-HOC NETWORK - SINGH, BHARAT (2014)
This thesis presents an approach for incident detection and management in Vehicular ad-hoc network (VANET). The study of incident detection has become one of the challenging subjects in VANET due to high speed communications with unpredictable vehicle network topology changes. Hence, incident detection and management is required to address this challenge. The new approach incident detection and management,known as early detection of incident (EDI) which aims at responding quickly to detection of incident and maintaining its connectivity to internet, is presented in this thesis. Early Detection of incident (EDI) extends the functionality of the existing Automatic Incident Detection (AID) which does not utilize the vehicular ad-hoc network resources optimally and cannot integrate with the internet arising end user information about incident detection and management. The early detection of incident has three distinct aspects compared to the existing techniques such as AID, NOTICE, and Distributed Automated Incident Detection with Vgrid.